The Islamic point of view on the concept of blessing and its significance in the educational process - Wail Mu'in Isma'il,; Rahimi Muhammad Saad,; Zawawi Ismail, (Faculty of Education, Universiti Kebangsaan Malaysia, 2011)
The absence of the concept of blessing in the field of education in our modern-day and the wrong perception of it has led to many problems faced by our education system at various stages, and it is also a key factor in the lack of stability and growth in the production of knowledge and lagging behind by looking back at our nobles scientists in spite of progress and technology that God bestow on mankind of our time. Moreover, the absence of Islamic texts and the traditions of prophet S.W.T as well as the teaching methodology and curriculum of our righteous predecessors in our education system have contributed significantly to the declination of science among the Muslim community in the contemporary world. This study aims to explain the Islamic point of view on the concept of the blessing, and the educational goals that the Islamic concept of blessing brings about into our education system. the researcher have collected, reviewed and analyzed many Islamic texts and extracted the concepts and the educational goals from those texts and sensitized them into nine concepts or categories as follows: Knowledge is associated with faith, understanding and prudence, sincere intention in seeking knowledge, avoiding argumentation, stick with the (group) and stay away from division, follow the ways of nobles scientists, giving credit to the original writer, give pride to knowledge, respect the time and take opportunity of the time and organize your time, habituate yourself to getting up early. The Researcher found out that the educational objectives related to these concepts can improve the level of understanding and awareness among students and raise the level of production and proof of the divine goodness in it (the blessing).